The Obligation to Report Cases of Child Sexual Abuse – Comparison of Legal Regulations in Poland, Austria, and the Federal Republic of Germany - Tuora-Schwierskott, Ewa; Bień-Węgłowska, Iwona Magdalena (Review of European and Comparative Law, 2023)
The subject matter of this work constitutes the comparison of the legal regulations governing the obligation to report cases of child sexual abuse in Poland, Austria, and the Federal Republic of Germany. The authors have focused on the analysis of the method of reporting the crime of paedophilia, the legal and social consequences of the failure to notify of that kind of offence, and the differences in the legislative, administrative, social, and educational measures taken to protect a child’s welfare.